Production and evaluation of lignocellulosic residue briquettes - Paula, Luana Elis de Ramos e (2011)
This study aimed to produce and evaluating the briquettes made from residues of plant biomass and test different times and temperatures. The material utilized was composed of wood processing residues (wood shaving and sawdust), coffee bean parchment and coffee tree stem, beam stem and pod, soybean stem and pod, rice husk, corn leaf, stem, straw and cob and sugar cane straw and bagasse. Briquetting was performed at a pressure of 150 Bar. Different times were tested for briquetting sawdust from wood and different temperatures for rice husk and parchment coffee. For evaluation of the briquettes quality, the apparent relative density, compression resistance and combustion index were determined. The results indicated that the briquetting time and temperature interfered in the mechanical resistance of the briquettes. The best pressing time was of eight minutes and the temperature of 125 °C. The briquettes produced from rice husk presented higher density and high mechanical density. The highest combustion index was found for the bean pod briquettes.doi: 10.4336/2011.pfb.31.66.103